Site-specific insertion of biologically functional adventitious genes into the Streptomyces lividans chromosome. - Omer, C A (1988)
We report that transformation of Streptomyces lividans with cloned DNA of the SLP1 genetic element results in integration of the element at the same chromosomal locus (attB) normally occupied by SLP1 in its original host, Streptomyces coelicolor, and in S. lividans that has received SLP1 by mating. We constructed SLP1 derivatives that can integrate foreign DNA at the attB site and used these to introduce adventitious DNA sequences into the S. lividans chromosome. We also identified three regions of SLP1 essential for its integration and demonstrated that integration of the SLP1 element does not require expression of functions necessary for stable maintenance or transfer of extrachromosomal forms of SLP1.